Some Properties of Certain Class of Analytic Functions - Uzoamaka A. Ezeafulukwe; Maslina Darus (International Journal of Mathematics and Mathematical Sciences)
We obtain some properties related to the coefficient bounds for certain subclass of analytic functions. We also work on the differential subordination for a certain class of functions.